2004
DOI: 10.1029/2004gl019608
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growing season and summer greenness on northern forests

Abstract: [1] We investigate the physiological effects of the elongation of the growing season and the increase in summer greenness on northern hemisphere forests by examining the relationship between NDVI and tree rings. These variables are correlated during June and July only. These results suggest that NDVI proxies the physiological status of trees and that the summer status of the canopy has a larger effect on tree vigor than the duration of the canopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
50
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 20 publications
13
50
0
Order By: Relevance
“…Vedin (1990) noted when studying the GS in northernmost Sweden in two 10-year periods, one warm (1931)(1932)(1933)(1934)(1935)(1936)(1937)(1938)(1939)(1940) and one colder (1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988), that GSL was shorter in the warm period than the cold one. Also, examining the relationship between NDVI and tree rings in North America and Eurasia, Kaufmann et al (2004) suggested that summer temperatures were more important to tree growth than the duration of the GS.…”
Section: General Trends In the Gbamentioning
confidence: 98%
“…Vedin (1990) noted when studying the GS in northernmost Sweden in two 10-year periods, one warm (1931)(1932)(1933)(1934)(1935)(1936)(1937)(1938)(1939)(1940) and one colder (1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988), that GSL was shorter in the warm period than the cold one. Also, examining the relationship between NDVI and tree rings in North America and Eurasia, Kaufmann et al (2004) suggested that summer temperatures were more important to tree growth than the duration of the GS.…”
Section: General Trends In the Gbamentioning
confidence: 98%
“…Both NDVI and EVI are direct optical measures of canopy greenness, are highly correlated with plant photosynthesis and chlorophyll content, and have been widely used to quantify vegetation dynamics and their responses to climate change [32][33][34][35][36][37][38][39][40]. The MODIS VI data from Terra (MOD13A1) and Aqua (MYD13A1) represent the best quality retrievals at a local solar time of~10:30 and~13:30, respectively.…”
Section: Satellite Datamentioning
confidence: 99%
“…Early work by Kaufmann et al [50] based on GIMMS data equally showed a positive correlation between tree-rings and NDVI over the entire growing season and monthly values for April-July and October. Nevertheless, the positive and robust relationship observed [40], respectively.…”
Section: Relationship Between Rwi-ndvimentioning
confidence: 99%
“…Early work by Kaufmann et al [50] based on GIMMS data equally showed a positive correlation between tree-rings and NDVI over the entire growing season and monthly values for April-July and October. Nevertheless, the positive and robust relationship observed between radial growth and NDVI identified for 69 sites across the Northern Hemisphere at the local level cannot be considered a rule on the global scale [7].…”
Section: Relationship Between Rwi-ndvimentioning
confidence: 99%